Thule Riometer Observations of Polar Cap Absorption Events (1962-1972) - Cormier, Raymond J (1973)
Polar Cap Absorption (PCA) events have been observed at Thule, Greenland, using a ground-based riometer for the past decade. The riometer was operated at a fixed frequency of 30 MHz, and used a two-element Yagi antenna directed toward the zenith. This report provides information for operational systems personnel and systems designers concerning the mean behavior of PCAs and other aspects of the phenomenon; for example, the extreme cases in duration and magnitude. In addition, included as an appendix are plots of dB absorption and proton flux (obtained from satellites) versus time for each event. The total number of events is 29.